2019
DOI: 10.1186/s12889-019-8030-4
|View full text |Cite
|
Sign up to set email alerts
|

Community awareness of diet needs associated with hypertension and type 2 diabetes mellitus in Hatcliffe, Zimbabwe

Abstract: BackgroundDiet is an important modifiable risk factor for non-communicable diseases (NCDs) like hypertension (HTN) and type 2 diabetes mellitus (T2DM). A NCD is a disease that cannot be transmitted from person to person. Dietary risk factors account for 5.8% of all-cause mortality in Sub-Saharan Africa (SSA). There has been an increase in the consumption of ‘westernized ‘diets in SSA. The westernized diets consumed in low-income countries are usually high in salt content, fatty, processed and fast foods; and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
(35 reference statements)
0
3
1
Order By: Relevance
“…37 Thus, the economic situation might have masked the true picture in terms of the actual connection between adherence to diet and hypertension control which was noted to be poor in another local study. 38 Despite the relationship between fat intake and BP control not being statistically significant, nearly seven in every 10 of the participants never/rarely consumed food with saturated fats like deep fat fried food, while 49% never consumed boiled meat with high-fat content and 93% rarely/never ate from fast-food outlets or restaurants in this study. This concurs with a study conducted in Ethiopia, where almost all participants rarely or never consumed food that contained high saturated fat.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…37 Thus, the economic situation might have masked the true picture in terms of the actual connection between adherence to diet and hypertension control which was noted to be poor in another local study. 38 Despite the relationship between fat intake and BP control not being statistically significant, nearly seven in every 10 of the participants never/rarely consumed food with saturated fats like deep fat fried food, while 49% never consumed boiled meat with high-fat content and 93% rarely/never ate from fast-food outlets or restaurants in this study. This concurs with a study conducted in Ethiopia, where almost all participants rarely or never consumed food that contained high saturated fat.…”
Section: Discussioncontrasting
confidence: 56%
“… 37 Thus, the economic situation might have masked the true picture in terms of the actual connection between adherence to diet and hypertension control which was noted to be poor in another local study. 38 …”
Section: Discussionmentioning
confidence: 99%
“…18 In addition, our previous cross-sectional study targeting the same group of participants found an association between resilience and social support and burnout. 6 Previous studies have found a positive association between resilience and social support among nurses 19 but, although decline in social support during the COVID-19 crisis is considered a risk factor for nurse burnout, 20 there is little research that looks at these factors together; namely, resilience intervention, social support, and nurse burnout. In particular, when addressing burnout in the COVID-19 pandemic, the utilization of online interventions can help prevent face-to-face droplet infection and contact transmission.…”
Section: Health; Online Systems; Organization and Administrationmentioning
confidence: 99%
“…A three-fold increase in reported cases of diabetes occurred during the 1990s in Zimbabwe [44]. In Zimbabwe, lifestyle changes caused by urbanisation and the westernisation of diets have been contributing to increases in Type 2 diabetes [45]. Development of combined antiretroviral therapy has led to the increase in the life span of PLHIV with treatment, similar to the expected age of the general population.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…With longevity, however, PLHIV are developing other chronic medical conditions, and one of these chronic comorbidities is diabetes mellitus [46]. Lifestyle-related risk factors which account for about 5.8% of all-cause mortality in sub-Saharan Africa are modifiable, unlike genetic-related risk factors [45]. Thus, the identified risk factors associated with the development of diabetes in PLHIV that are similar to persons without HIV, such as older age, heredity, higher Body Mass Index [BMI], higher triglyceride and hypertension.…”
Section: Diabetes Mellitusmentioning
confidence: 99%